Hospital Management Information System in Increasing Efficiency - Andwika, Ida Bujangga; Yundari, Eli; Florenza, Yolla (IC-ITECHS, 2024)
Healthcare services are the main topic because of the high complexity challenges in the health sector. The purpose of this study is to determine the implementation of Hospital Information System (HIS) in increasing the efficency of healthcare services. The research design used in this article is a literature review method related to Hospital Information Systems in supporting the efficiency of hospital services using databases. In this study, the researcher collected literature review data with a thematic structure based on the concept of thinking using the keywords "hospital information system", "information system efficiency", and "healthcare efficiency" which were compiled to answer scientific questions by grouping and discussing literature sources accordingly to the theme or topic. The results showed that Hospital Information System can minimize the complexity of healthcare services by increasing organizational efficiency through innovation in developing information system based on business process management, service automation, reducing costs, improving hospital performance, which aims to develop human resources, organizational development, and technological quality improvement to achieve efficency in healthcare services.